Human Resource Management Practices and Employee Retention in Nepalese Commercial Banks: Evidence from the Far-Western Province - Kunwar, Nrip Bahadur; Bhandari, Avishek (BMC Research Journal, 2026)
Employee retention has become a significant strategic issue in the banking industry as a result of growing competition, employee mobility, and heightened expectations of employees. This study aims to examine the effect of human resource management (HRM) practices on employees’ retention in the commercial banks in Nepal in the Far Western Province. The key HRM practices that are focused on in the study include training and development, compensation and benefits, performance appraisal, work environment, organizational culture, and employee empowerment. Using descriptive and explanatory research design, primary data was collected from 180 employees of some selected commercial banks using structured questionnaires. Statistical tools such as descriptive analysis, correlation and multiple regressions were used to analyze the data. The findings reveal that compensation, work environment, and empowerment of the employees have a significant positive effect on the retention of employees, whereas training and performance appraisal have a moderate effect on the retention of employees. The study concludes that good HRM practices are vital for retaining skilled employees in geographically disadvantaged regions such as the Far Western Province. The findings make significant contributions to HR managers and policy makers in designing HR strategies that focus on retention in the Nepalese banks.